2022
DOI: 10.21203/rs.3.rs-1938551/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning curve of robot-assisted total knee arthroplasty and its effects on implant position in Asian patients: A prospective study

Ho Jung Jung,
Min Wook Kang,
Jong Hwa Lee
et al.

Abstract: Background Robot-assisted total knee arthroplasty (r-TKA) can reportedly achieve a more accurate implant position than conventional total knee arthroplasty (c-TKA), although its learning curve is controversial. Moreover, there are few studies on Asians with different anatomical characteristics. This study aimed to determine the learning curve for r-TKA and compare implant positions between r-TKA and c-TKA according to the learning curve in Asian patients. Methods This prospective study included 50 consecutiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Finally, this study included the initial cases from the learning curve of the robotic arm‐assisted system. However, a previous study confirmed that the final implant positions and outliers were not significantly different between the initial cases and proficiency cases [16]. Therefore, it was determined to be reliable even though the initial cases were included.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Finally, this study included the initial cases from the learning curve of the robotic arm‐assisted system. However, a previous study confirmed that the final implant positions and outliers were not significantly different between the initial cases and proficiency cases [16]. Therefore, it was determined to be reliable even though the initial cases were included.…”
Section: Discussionmentioning
confidence: 91%
“…RTKA is known for its advantages, such as accurate implant positioning and fewer outliers. Jung et al [16] confirmed that RTKA resulted in fewer position errors in the sagittal tibial component and femoral component rotation as well as fewer outliers in the hip‐knee‐ankle angle, coronal femoral component position, sagittal tibial component position and femoral component rotation position. However, the relationship between accurate implant positioning and clinical outcomes remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Correction: BMC Musculoskelet Disord 24, 332 (2023) https://doi.org/10.1186/s12891-023-06422-w Following publication of the original article [1], the authors identified the following minor typographical errors in Tables 1 and 3, which are not significant regarding result. Table 1: K-L grade IV (%) -> K-L grade (III/IV) Table 3: HKA angle of proficiency stage: 1/32 (6%) -> 1/32 (3%)…”
Section: Publisher's Notementioning
confidence: 99%